The relationship between e-shopper typologies and online buying satisfaction among undergraduate students in Klang Valley public universities - Iskandar, Aina Farhana; Ma’rof, Aini Azeqa; Rosnon, Mohd Roslan (Human Resources Management Academic Research Society, 2024)
This study explores the relationship between e-shopper typologies and online buying satisfaction among undergraduate students in Klang Valley public universities, Malaysia. Utilizing a survey methodology, data were collected from 408 students to identify their eshopper typology—Convenience Shoppers, Variety Seekers, Store-oriented Shoppers, and Balanced Buyers—and measure their satisfaction with online buying experiences. The research aimed to understand how distinct shopping behaviors influence satisfaction levels and to delineate which factors most significantly impact these outcomes. Findings indicate that different shopper typologies have varied satisfaction outcomes, with Convenience Shoppers and Balanced Buyers showing higher satisfaction levels, suggesting the need for e-commerce platforms to tailor experiences that cater to the diverse preferences of young adult consumers. The study contributes to consumer behavior literature by providing insights into the underexplored area of youth e-shopping behaviors and their satisfaction with online shopping, highlighting implications for e-commerce strategies tailored to meet the unique needs of this demographic.